Interface Design and User Experience in Selalulaku Applications Using Lean UX Methods - Widyo Trenggono, Brahmantio (Information Technology International Journal, 2023)
Consumptive behaviour often occurs in the younger generation, where changes in appearance and lifestyle have become essential today, especially in purchasing goods online. Online shopping events in Indonesia are interesting to study further because they have become a habit or trend for the younger generation, especially since they are easy to access anytime and anywhere. User interface and user experience are essential things that are useful for making it easier for users to operate applications, obtain responses from application services, and meet and understand user needs. Therefore, this research aims to design the user interface and user experience of the mobile-based Selalulaku application using the Lean UX method. This research found that the overall average score was 1.34, with a comparative value of "Good". So, it can be said that the interface design and user experience regarding efficiency, functionality and appearance received a "Good" rating.